Analisis Pengelolaan Konferensi Nasional Pendekatan Business Process Management Menggunakan Value-Added Analysis dan Root-Cause Analysis - Salsabilah, Zafira; Budi Susanto, Agung; Taryo, Taswanda (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2023)
Conference management is one of the core business processes at the Research and Community Service Institute (LPPM) and it is conducted by online. The problem is the lack of a business process model for conference management, hence the committee had not a clear understanding of its activities. Furthermore, there has been no evaluation of the business processes, leading to unidentified weaknesses in the activities. The purpose of this research is to map and summarize the business processes using Business Process Management (BPM). BPM proves to be suitable for achieving the research objectives as it focuses on process approaches and provides tools and techniques to enhance the quality of conference management. The analysis employs qualitative process analysis with Value-Added Analysis and Root-Cause Analysis using the Why-Why Diagram approach to identify the root causes of issues and propose improvement measures for each business process. The research methodology used is qualitative with data collection technique involving interview, observation, and literature studies. The business process modeling adopts the Business Process Modelling Notation (BPMN). The research outcome presented a to-be process model that illustrated the recommended conference management business process which consisting of 7 main business processes, 27 sub-processes, 21 activities, and 200 tasks.